Pricing Strategy for Services Using the Tripod Method at the Tutoring Study Point - Nuniek Dewi Pramanik; Dian Candra Fatihah; Sa'ad Noor; Yoga Rema Putra (CV Edujavare Publishing, 2026)
This research aims to analyze the service pricing strategy at the Tutoring Learning Point using the Tripod method, which is expected to provide benefits for tutoring pioneers in a more structured and data-based prices setting. Many new business actors, including those in the education sector, often set prices based only on estimates without careful calculations regarding costs and market value. A qualitative approach with descriptive analysis was used to explore the factors that influence price determination, by collecting data through in-depth interviews and Focus Group Discussions (FGD) with managers, teachers and students. The research results show that cost analysis (Cost-Based Pricing) produces a minimum price of IDR 360,000 per student per month, which includes operational costs such as tutor salaries, place rental and learning material costs. Value analysis (Value-Based Pricing) shows that the majority of respondents consider a reasonable price for tutoring services to be between IDR 400,000 to IDR 600,000 per month, with superior facilities that increase the perception of value. Meanwhile, competition analysis (Competitor-Based Pricing) found that the average price of competitors was in the range of IDR 350,000 to IDR 450,000. Taking into account the superiority of the services offered, the price of IDR 450,000 per student per month is considered optimal and reflects a balance between operational costs and customer perceived value.